Determination of Wair in high‐energy electron beams using graphite detectors. Issue 11 (28th September 2019) - Bourgouin, Alexandra; Cojocaru, Claudiu; Ross, Carl; McEwen, Malcolm
Abstract : Purpose: ICRU Report 90 on Key Data for Ionizing‐Radiation Dosimetry: Measurement Standards and Applications (2014) has reaffirmed the recommended value of the mean energy required to create an ion pair in air, W air, to be 33.97(12) eV. The report also indicates that this "constant" of radiation dosimetry is energy independent above 10 keV, since there is no theoretical or experimental evidence to the contrary. The goal of this investigation is to obtain additional experimental determinations of W air in high energy beams and thus to verify the suggested energy independence. Methods: W air can be evaluated by combining ionometric and calorimetric measurements with a calculated ratio of the absorbed dose in the ion chamber air cavity and that of the calorimeter absorbing element. In this investigation, a graphite parallel plate chamber and a graphite calorimeter were used and the dose ratio was calculated using the EGSnrc Monte Carlo code. Measurements were made in electron beams from the NRC Vickers linear accelerator at two incident energies, 20 and 35 MeV. A range of average energies at the measurement point were obtained by inserting graphite plates in the primary beam. Results: The average value of W air obtained in this investigation is 33.85(18) eV which is consistent with the recommended value of 33.97(12) eV where the number in brackets represents the combined standard uncertainty of the value, referring to the corresponding last digits. The individual values of W air do not show any statistically significant energy dependence. Conclusion: The overall combined uncertainty of 0.5% meets the original target of the investigation. A larger‐scale investigation, involving more individual energy points and a wider range of electron energies is required to go further and, for example, comment on the W air energy dependency question raised by Tessier et al. [Med. Phys. 2018;45 :370–381]. Abstract :